(untitled) (Medical Forum Monthly, 2023)
Objective: The basic aim of the study is to find the endoscopic sinus surgery outcomes in patients with chronic rhinosinusitis and immunoglobulin deficiencies. Study Design: retrospective study Place and Duration of Study: This study was conducted at the Shalamar Medical and Dental College, Lahore from June 2022 to June 2023. Materials and Methods: The study included a total of 220 patients. Patient data for this retrospective study were collected meticulously from the records maintained at Fatima Memorial Hospital, Lahore. The data collection process adhered to rigorous standards to ensure accuracy and completeness. Information on patient demographics, including age and gender, was recorded for all 220 individuals included in the study. Results: The study population of 220 patients includes a diverse range of ages, with a median age of 42 years. Gender distribution is approximately equal, with 50.5% male and 49.5% female patients. The majority of patients (75%) have common variable immunodeficiency (CVID), while the remaining (25%) have selective IgA deficiency. Pre-operative assessments reveal that all patients presented with moderate to severe CRS symptoms, including nasal congestion, facial pain, and olfactory disturbances. The average Lund-Mackay score at the pre-operative stage was 15, indicative of significant sinus involvement. Conclusion: It is concluded that these findings provide a platform for discussing the potential outcomes of ESS in CRS patients with immunoglobulin deficiencies. These insights underscore the importance of a multidisciplinary approach to patient care, diligent long-term follow-up, and the need for individualized treatment strategies in managing this medically complex patient population.